Hubungan Dukungan Keluarga dengan Keaktifan Lansia dalam Mengikuti Kegiatan Senam Lansia di Posyandu Lansia Wilayah Kerja Puskesmas Sawit Kabupaten Boyolali - Windiah Nur Kusumaningtyas; Erika Dewi Noorratri (Yayasan Literasi Sains Indonesia, 2022)
Elderly exercise is beneficial for improving the health of the elderly. Gymnastics for the elderly has 5M properties (cheap, easy, mass, lively and beneficial) which is able to attract the elderly to follow it. Family support is the attitude, action and acceptance of the family to support and provide assistance in the form of emotional, informational, instrumental and assessment support. Family support plays an important role in encouraging the activity of the elderly to participate in the Integrated Healthcare Center activities for the elderly. To determine the relationship between family support and the activity of the elderly in participating in elderly gymnastics at the Integrated Healthcare Center for the elderly in the work area of ​​the Sawit Health Center, Boyolali Regency. The type of research used is a correlation design with a cross sectional design. The sample used in this study was 79 respondents based on the theory of inclusion and exclusion. Based on the results of the bivariate chi square test, the p value < p (0.000) means that there is a relationship between family support and the activity of the elderly in participating in elderly gymnastics at the Integrated Healthcare Center for the elderly in the work area of ​​the Sawit Health Center, Boyolali Regency. There is a relationship between family support and the activity of the elderly in participating in elderly gymnastics at the elderly Integrated Healthcare Center in the work area of ​​the Sawit Health Center, Boyolali Regency.